Pijat Oksitosin untuk Meningkatkan Produksi ASI - Ardila; Melly Kurnia Sari; Risma Aliviani Putri; Heni Setyowati (Universitas Ngudi Waluyo, 2024)
The problem of lack of breast milk production in postpartum mothers is very often found. This is due to postpartum mothers' lack of knowledge about oxytocin massage. Apart from that, the hospital has never carried out education or counseling regarding oxytocin massage for postpartum mothers to facilitate or increase breast milk production. This service aims to carry out oxytocin massage activities for postpartum mothers and evaluate knowledge of oxytocin massage for postpartum mothers.This community service method is pre-test, practice and post-test. The target of this service research uses a sample of 10 postpartum mother respondents at Tidar Hospital, Magelang City. This service will be held from 2 September to 8 September. The aim of this community service is to increase post partum mothers' knowledge about oxytocin massage to overcome breast milk problems and increase breast milk production after being given health education or health counseling. The implementation of activities is carried out in three stages, namely problem, solution and evaluation. Based on the results of the pre-test and post-test, the results showed that there was an increase in post-partum mothers' knowledge about oxytocin massage to overcome breastfeeding problems and increase breast milk production after being given health education or health counseling. The suggestion for continuing this activity at the next stage is to coordinate with the head of the room to provide oxytocin massage training in an effort to overcome the problem of lack of breast milk production more effectively, efficiently and comprehensively. Abstrak Permasalahan kurangnya produksi ASI pada ibu postpartum sangat sering ditemukan. Hal tersebut dikarenakan kurangnya pengetahuan ibu postpartum tentang pijat oksitosin. Selain itu pelaksanaan edukasi atau penyuluhan tentang pijat oksitosin pada ibu nifas untuk memperlancar atau meningkat produksi ASI belum pernah dilakukan oleh pihak rumah sakit. Pengabdian ini bertujuan untuk melaksanakan kegiatan pijat oksitosin pada ibu post partum dan melakukan evaluasi pengetahuan pijat oksitosin pada ibu postpartum. Metode pengabdian masyarakat ini yaitu pre test, praktik dan post tes. Sasaran Penelitian pengabdian ini menggunakan sampel sebayak 10 responden ibu postpartum di RSUD Tidar Kota Magelang. Pengabdian ini dilaksanakan pada bulan 2 September- 8 september 2024. Tujuan dari pengambdian masyarakat ini apakah terjadi peningkatan pengetahuan ibu post partum tentang pijat oksitosin untuk mengatasi permasalahan ASI dan meningkatkan produksi ASI sesudah diberikan pendidikan kesehatan atau penyuluhan kesehatan. Pelaksanaan kegiatan dilaksanakan tiga tahap yaitu permasalahn, solusi dan evaluasi. Berdasarkan hasil pre test dan post test menunjukkan hasil bahwa terjadi peningkatan pengetahuan ibu post partum tentang pijat oksitosin untuk mengatasi permasalahan ASI dan meningkatkan produksi ASI sesudah diberikan pendidikan kesehatan atau penyuluhan kesehatan. Saran untuk kelanjutan kegiatan ini pada tahapan berikutnya yaitu dengan mengkoordinasikan dengan kepala ruang untuk dapat memberikan pelatihan pijat oksitosin dalam upaya mengatasi permasalah kurangnya produksi ASI secara lebih efektif, efisien dan menyeluruh.